The Effect of Village Fund Allocation on the Development and Welfare of Village Communities in Penanae Village, Raba District, Bima City - Ananda Salsa Nurillah; Rustan, Rustan; Faidul Adziem (International Journal of Economic Research and Financial Accounting, 2024)
This research is a type of quantitative research with the aim of finding out the effect of village fund allocation on the development and welfare of village communities in Penanae Village, Raba District, Bima City. This sample was taken from Penanae Village, Raba District, Bima City. The type of data used in this research is quantitative data obtained from questionnaires distributed and related to the problem being studied. Data collection was carried out by observation and distribution of questionnaires. In this research, the data sources used in data collection include secondary data. Based on the results of data research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 27 application regarding the influence of village fund allocation on the development and welfare of the Bima community which was discussed in the previous chapter, the author draws important conclusions, namely (1) there is an influence village fund allocation on village development, (2) there is a significant influence between village fund allocation on community welfare, (3) there is a significant influence between village fund allocation and village development and community welfare. Suggestions for the government to be more able to embrace the community in village development to improve the welfare of the community.